2007
DOI: 10.1038/nrc2070
|View full text |Cite
|
Sign up to set email alerts
|

The Salvador–Warts–Hippo pathway — an emerging tumour-suppressor network

Abstract: Intense research over the past four years has led to the discovery and characterization of a novel signalling network, known as the Salvador-Warts-Hippo (SWH) pathway, involved in tissue growth control in Drosophila melanogaster. At present, eleven proteins have been implicated as members of this pathway, and several downstream effector genes have been characterized. The importance of this pathway is emphasized by its evolutionary conservation, and by increasing evidence that its deregulation occurs in human t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
613
2
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(626 citation statements)
references
References 92 publications
8
613
2
3
Order By: Relevance
“…Although cell death was attributed to aberrant regulation of H-Ras, JNK and nuclear factor-kB, PRX-Imediated MST1 activation probably also takes part in this process, and further examinations of these pathways could facilitate the development of better chemotherapeutic agents. Recent studies have indicated the importance of a mammalian signaling pathway equivalent to the Drosophila Hippo pathway in tumor suppression (Harvey and Tapon, 2007;Zeng and Hong, 2008). In Drosophila, Hippo activates Warts (LATS1/2 in mammals) together with Salvador (WW45 in mammals).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cell death was attributed to aberrant regulation of H-Ras, JNK and nuclear factor-kB, PRX-Imediated MST1 activation probably also takes part in this process, and further examinations of these pathways could facilitate the development of better chemotherapeutic agents. Recent studies have indicated the importance of a mammalian signaling pathway equivalent to the Drosophila Hippo pathway in tumor suppression (Harvey and Tapon, 2007;Zeng and Hong, 2008). In Drosophila, Hippo activates Warts (LATS1/2 in mammals) together with Salvador (WW45 in mammals).…”
Section: Discussionmentioning
confidence: 99%
“…Activated Warts then excludes an oncogenic transcription factor Yorkie (YAP in mammals) from the nucleus and induces apoptosis. The Hippo pathway appears to be conserved in mammals, and the human genes for several pathway components have been found to be mutated in cancers (O'Neill et al, 2005;Harvey and Tapon, 2007;Zeng and Hong, 2008). PRX-I is also suggested to suppress cancer development because mice lacking the PRX-I gene have a short life span owing to frequent development of several cancers (Neumann et al, 2003;Egler et al, 2005;Graves et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In mammals, recent studies have established a role for this pathway in regulating cell contact inhibition, organ size control, and cancer development. [4][5][6] The Hippo pathway is activated upon sensing of cell-cell contact via cell surface molecules.…”
mentioning
confidence: 99%
“…Over the past decade Ste20-like kinases, MOB proteins, and LATS/NDR kinases have gained even more attention, since Hippo (a GCK-II Ste20-like kinase), Mats/dMOB1, and Warts/Lats (one of two LATS/NDR kinases in flies) have been established as the central signalling module of the Hippo tumour suppressor signalling cascade in Drosophila melanogaster [21][22][23]. Loss of Hippo, Mats or Warts could be functionally compensated by their mammalian counterparts MST2, LATS1 and MOB1A, respectively [24][25][26], strongly suggesting that, similar to the MEN/SIN, Hippo signalling is very highly conserved from flies to humans.…”
Section: Introductionmentioning
confidence: 99%